The Effect of Sambung Nyawa Leaf Extract (Gynura Procumbens) on Albumin and Globulin of Rats (Rattus Novergicus) Serum Induced by E. Coli Bacteria - Disa R Siregar; Pasar Maulin Silitonga (Universitas Negeri Medan, 2021)
The aim of this research was to study the effect of extract of the sambung nyawa (Gynura procumbens) leaf on albumin and globulin concentration of rats blood serum. The research method is experimental used Completely Randomized Design (CRD) that consists of 3 treatments and 5 replications. The treatment of this research was induced rats with E. coli then given 0.5 mL of sambung nyawa leaf extract with doses 0.0 mg/kgBW; 300 mg/kgBW; and 600 mg/kgBW. The data was analyzed using Analysis of Variance. The results showed that the giving extract of the sambung nyawa leaves gives effect on albumin and globulin concentration of rats blood serum. Giving sambung nyawa leaf extract at dose 0.00 mg/kgBW; 300 mg/kgBW; and 600 mg/kgBW to rats gave the average of albumin and globulin concentration in a row in each treatment is 486 g/dL; 2.632 g/dL; 4.23 g/dL and 5.82 g/dL; 6.03 g/dL; 4.16 g/dL.